2014
DOI: 10.1111/pbi.12245
|View full text |Cite
|
Sign up to set email alerts
|

A novel noninvasive procedure for high‐throughput screening of major seed traits

Abstract: SummaryThe large numbers of samples processed in breeding and biodiversity programmes require the development of efficient methods for the nondestructive evaluation of basic seed properties. Near-infrared spectroscopy is the state-of-the-art solution for this analytical demand, but it also has some limitations. Here, we present a novel, rapid, accurate procedure based on time domain-nuclear magnetic resonance (TD-NMR), designed to simultaneously quantify a number of basic seed traits without any seed destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…5, option 6), however, would need only pick and place, which is much faster. To monitor different traits of interest beyond morphological ones, additional sensors could be implemented: near-infrared spectroscopy to analyze the chemical content of seeds (Agelet and Hurburgh, 2014); chlorophyll fluorescence to score seed maturity and performance (Jalink et al, 1998); spectral imaging to classify common wheat (Triticum aestivum) and durum wheat (Triticum durum; Benoit et al, 2016); low-field NMR to measure both solid and liquid parts of a seed, as demonstrated for growing bean (Phaseolus vulgaris) pods (Windt and Blümler, 2015), or chemical components, such as lipids, carbohydrates, and proteins (Rolletschek et al, 2015); or x-ray CT to image internal seed structures, allowing, for example, the detection of internal defects of seeds (Stuppy et al, 2003;Belin et al, 2011;Yamauchi et al, 2012;Verboven et al, 2013). Further developments of phenoSeeder can be followed at www.phenoseeder.de.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5, option 6), however, would need only pick and place, which is much faster. To monitor different traits of interest beyond morphological ones, additional sensors could be implemented: near-infrared spectroscopy to analyze the chemical content of seeds (Agelet and Hurburgh, 2014); chlorophyll fluorescence to score seed maturity and performance (Jalink et al, 1998); spectral imaging to classify common wheat (Triticum aestivum) and durum wheat (Triticum durum; Benoit et al, 2016); low-field NMR to measure both solid and liquid parts of a seed, as demonstrated for growing bean (Phaseolus vulgaris) pods (Windt and Blümler, 2015), or chemical components, such as lipids, carbohydrates, and proteins (Rolletschek et al, 2015); or x-ray CT to image internal seed structures, allowing, for example, the detection of internal defects of seeds (Stuppy et al, 2003;Belin et al, 2011;Yamauchi et al, 2012;Verboven et al, 2013). Further developments of phenoSeeder can be followed at www.phenoseeder.de.…”
Section: Discussionmentioning
confidence: 99%
“…This might be true even when considering that the type of reserves, such as proteins, carbohydrates, or lipids (Rolletschek et al, 2015), and also different seed tissues, such as seed coat, embryo, or endosperm, may contribute differently to seed mass (Alonso-Blanco et al, 1999). While seed mass and time to germination (radicle protrusion) do not necessarily correlate (Norden et al, 2009), in particular under greenhouse conditions, higher seed mass may be advantageous for seedling establishment under adverse environmental conditions (Moles et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of high-field NMR to screen seeds and grains based on their quality characteristics, that is, protein content and quality, is not always feasible due to complicated procedures required for sample preparation as well as the cost of the required instruments (Gouilleux, Marchand, Charrier, Remaud, & Giraudeau, 2018;Marcone et al, 2013). This technique has been mostly used for quality characterization and screening of oilseeds (Horn et al, 2011;Melchinger et al, 2017Melchinger et al, , 2018Pedersen, Munck, & Engelsen, 2000), although a few studies have been conducted to examine the possibility of using LF-NMR for cereal screening (Brusewitz & Stone, 1987;Rolletschek et al, 2015). This technique has been mostly used for quality characterization and screening of oilseeds (Horn et al, 2011;Melchinger et al, 2017Melchinger et al, , 2018Pedersen, Munck, & Engelsen, 2000), although a few studies have been conducted to examine the possibility of using LF-NMR for cereal screening (Brusewitz & Stone, 1987;Rolletschek et al, 2015).…”
Section: Resonance Spectroscopymentioning
confidence: 99%
“…Namely, a database focusing on the accumulation of NMR spectra from various food processing sources has not been constructed till date. Therefore, we have started developing such a database using bench-top-type NMR with the intended future aim of in situ characterization at various production sites [24,25,26,27,28,29]. Simultaneously, we have accumulated subjective human data accompanied by physical property data.…”
Section: Introductionmentioning
confidence: 99%